2011
DOI: 10.1111/j.1574-6941.2011.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Eikelboom's morphotype 0803 in activated sludge belongs to the genus Caldilinea in the phylum Chloroflexi

Abstract: Micromanipulated filamentous bacteria from bulking and foaming activated sludge morphologically identified as Eikelboom type 0803 were shown to be affiliated to the genus Caldilinea within the phylum Chloroflexi. Specific FISH probes were designed for their in situ detection and quantification in seven Danish wastewater treatment plants with biological nutrient removal. The survey applied all species-specific probes for Chloroflexi of relevance in activated sludge treatment plants as well as the phylum-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 56 publications
2
80
0
1
Order By: Relevance
“…The potential for aerobic respiration Cfx-K genome annotation confirmed the potential for aerobic respiration (Supplementary Table S5; Figure 4). Although only few of the described Cfx-K-related species (of the classes Anaerolineae, Caldilineae and Ardenticatenia) are able to utilize oxygen as an electron acceptor (see Supplementary Table S4), aerobic uptake of substrates is a common feature of members of this phylum in full-scale activated sludge systems (Kragelund et al, 2007(Kragelund et al, , 2011 and was also confirmed in situ for the B45 phylotype in this study (see later). Figure 4 Metabolic model for members of the B45 phylotype in activated sludge.…”
Section: Surface Properties Of the B45 Phylotypesupporting
confidence: 53%
See 4 more Smart Citations
“…The potential for aerobic respiration Cfx-K genome annotation confirmed the potential for aerobic respiration (Supplementary Table S5; Figure 4). Although only few of the described Cfx-K-related species (of the classes Anaerolineae, Caldilineae and Ardenticatenia) are able to utilize oxygen as an electron acceptor (see Supplementary Table S4), aerobic uptake of substrates is a common feature of members of this phylum in full-scale activated sludge systems (Kragelund et al, 2007(Kragelund et al, , 2011 and was also confirmed in situ for the B45 phylotype in this study (see later). Figure 4 Metabolic model for members of the B45 phylotype in activated sludge.…”
Section: Surface Properties Of the B45 Phylotypesupporting
confidence: 53%
“…Whether or not B45 members directly contribute to the hydrolysis of complex carbon sources remains to be demonstrated. The aerobic utilization of complex organic material has been demonstrated for other members of the Chloroflexi in nutrient removal systems (Miura et al, 2007;Kragelund et al, 2011). Nitrite and nitrous oxide may both serve as alternate electron acceptors for the strain with the Cfx-K genome.…”
Section: Potential Storage Polymersmentioning
confidence: 99%
See 3 more Smart Citations